Development of a New ‘Engineering English for Intercultural Communication’ Online Course to Prepare New Engineers for Working in Intercultural Workplace Settings - Janenoppakarn, Chalida; Rajprasit, Krich (LEARN Journal: Language Education and Acquisition Research Network, 2025)
This study aimed to develop a tailor-made online course called “Engineering English for Intercultural Communication (EEIC)” for undergraduate engineering students based on the self-report on English language proficiency, intercultural communication competence (ICC) as well as needs of a diverse set of stakeholders in the engineering professions and education. It comprises two phases: (1) analyzing the data from the stakeholders, and (2) designing and developing a course. In the first phase, a mixed-methods approach was adopted. A questionnaire was employed for a self-report on English language proficiency and problems in language use, as well as the ICC of 108 Thai engineering students at an autonomous university in Thailand and 22 Thai engineering professionals working in international companies. Then, semi-structured interviews on the necessity of engineering English and ICC for novice engineers were conducted with 16 engineering course lecturers. The second phase involves the design and development of the EEIC course. The ADDIE model was adopted and the findings from the analysis of the data collected in the first phase were used to guide the design and develop such a course with four units, each with a different focus, specifically. This study contributes to the ELT field by showcasing a course design process to meet the needs of a set of diverse stakeholders. Specifically, the course was developed based on real-life information obtained from both educational and professional contexts analyzed to provide guidance for the course design and development.